The reality of remote exams during the Corona pandemic crisis from the point of view of students of King Khalid University - An evaluation study - Alansary, Areej Ibrahim (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the reality of remote exams during the Corona pandemic crisis from the point of view of the students of King Khalid University. The study followed the descriptive analytical method. the sample was chosen randomly. A questionnaire was prepared and distributed electronically after ensuring its validity and reliability. The study sample consisted of (456) female students from King Khalid University, The results of the study indicated that there were statistically significant differences at the level (0.05) between female students for the advantages of remote exams due to specialization and in favor of female students of scientific specialization, and the absence of significant differences between female students due to obstacles and challenges of remote exams due to specialization, and the absence of significant statistically significant differences between The female students for the proposals for developing remote exams are attributed to the specialization, and the presence of statistically significant differences in the opinions of female students in favor of the postgraduate students, and the presence of statistically significant differences in the opinions of female students in favor of the variable years of experience in the axes (excellence - obstacles - and future proposals) for the remote exams, and they also answered The results of the study questions for determining the advantages, challenges and obstacles of remote exams and the most important proposals for its development. The study recommended working on using the results of the study to enhance the application of remote exams in the future. Because of its positive advantages in supporting the measurement of student achievement, developing plans and programs to benefit from them, and establishing a mechanism for immediate technical support while performing remote exams in the e- learning deanships in Saudi universities.